The discussion of menopause in community: Providing opportunities for knowledge and concepts - Amaral, Cisnara Pires; Gazoni, Vanessa Fatima; Zortéa, Nagila Bernarda; Pinto, Douglas Bacin; Borba, Luana Casarotto de (Seven Editora, 2023)
We live in times that taking care of esthetics has become a standard in society, but there is still a lack of information regarding the cellular and metabolic dysfunctions that occur in the climacteric and menopausal phase. Thus, an Online Journey on Menopause was held during Esthetics and Cosmetics of the Regional Integrated University of Alto Uruguay and the Missions/URI, with the objective of providing opportunities for the protagonist women over 40 years of age, enabling discussions related to hormones and their consequences in the body. To this end, a partnership was made with the Academic League of Health and Environment (ALHE), registration in the event through the University’s website and contact with the volunteer speakers, namely: Biologist, Pharmacist, Doctor and Psychologist. To discuss the results, the Grounded Theory (GT) was chosen. It was noted that the activity had 75 registrations, that there was participation of women through interaction in the chat during the lectures, that the feedbacks received demonstrate that discussing menopause, providing opportunities for knowledge sharing and inserting academic knowledge in the community are primary prevention actions capable of enabling autonomy, criticality and protagonist action of mature women. DOI:https://doi.org/10.56238/globalhealthprespesc-080